46th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference 2005
DOI: 10.2514/6.2005-2224
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the Non-linear Impact Response of Flat and Curved Composite Panels

Abstract: The application of scaling laws to thin flat and curved composite panels exhibiting nonlinear response when subjected to low-velocity transverse impact is investigated. Previous research has shown that the elastic impact response of structural configurations exhibiting geometrically linear response can be effectively scaled. In the present paper, a preliminary experimental study is presented to assess the applicability of the scaling laws to structural configurations exhibiting geometrically nonlinear deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…It has been shown frequently in the literature that their value is independent of impact energy, and it stays constant for increasing values of available kinetic energy. [3][4][5][6]11 Furthermore, for modern composite systems, which are relatively strain-rate insensitive in this low-velocity regime, it has been found that the value of the critical force is very close to the mean static failure load (MSFL) of the laminate, obtained by means of quasi-static indentation tests.…”
Section: A Force-and Energy-time Historiesmentioning
confidence: 68%
See 4 more Smart Citations
“…It has been shown frequently in the literature that their value is independent of impact energy, and it stays constant for increasing values of available kinetic energy. [3][4][5][6]11 Furthermore, for modern composite systems, which are relatively strain-rate insensitive in this low-velocity regime, it has been found that the value of the critical force is very close to the mean static failure load (MSFL) of the laminate, obtained by means of quasi-static indentation tests.…”
Section: A Force-and Energy-time Historiesmentioning
confidence: 68%
“…3, but if the signal is very noisy, values of n up to 14 have been used. 4 One of the simplest smoothing techniques, as the one employed in the Dynatup 930 software, 21 takes a running average of the recorded signal over 2n + 1 points. In most cases, a value of n = 1-3 will produce satisfactory results, 11 as shown in Fig.…”
Section: Oscillations and Dynamic Signal Controlmentioning
confidence: 99%
See 3 more Smart Citations